PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KOMPENSASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Kiswanto, Desi Perwitasary, Seno Andri, (Jurnal Ilmu Administrasi Negara, 2020)
Effect of Situational Leadership Style and Compensation on the Performance of Civil Servants at the Regional Personnel Agency of Riau Province. The purpose of this study was to find out how the influence of situational leadership style and compensation on employee performance at the Regional Civil Service Agency of Riau Province. The results of the study show that partially the compensation variable is more dominant than the situational leadership style variable in influencing the performance of employees in the Regional Personnel Agency of Riau Province. While simultaneously situational leadership style and compensation affect the performance of employees of the Riau Provincial Personnel Agency. In this case the performance of employees of the Riau Province Regional Personnel Agency has been successfully improved by approaching situational leadership and compensation. Based on the regression coefficient test it is known that situational leadership style variables and compensation have a positive regression coefficient and prove its contribution to the performance of employees at the Regional Personnel Agency of Riau Province.